2022
DOI: 10.3390/toxics10090528
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Toxic Metal Pollution in Rivers on the Physiological Health of Fish

Abstract: Toxic metal pollution influences the lives of diverse aquatic organisms and humans who consume contaminated aquatic products. However, its potential impacts on aquatic organism health and, thus, ecological health, have been neglected in many regions. This research was carried out to contribute to filling that knowledge gap. Three freshwater fish species in the Nhue–Day River basin, Vietnam, have been chosen to study the bioaccumulation of metals (Zn, Cu, Pb, and Cd) in the tissues (livers, kidneys, gills) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Contaminated water causes not only morphological changes and damage to the function of gills but also biochemical changes. (Strzyzewska, 2016;Shah et al, 2020;Ngo et al, 2022) In this research, the level of proteins in all three organs decreased after exposure to heavy metals. Oxidative stress caused by heavy metals might have led to changes in protein metabolic processes, promoting protein catabolism.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Contaminated water causes not only morphological changes and damage to the function of gills but also biochemical changes. (Strzyzewska, 2016;Shah et al, 2020;Ngo et al, 2022) In this research, the level of proteins in all three organs decreased after exposure to heavy metals. Oxidative stress caused by heavy metals might have led to changes in protein metabolic processes, promoting protein catabolism.…”
Section: Discussionmentioning
confidence: 49%
“…These studies have reported that exposure to heavy metals is also manifested by changes in physiological and biochemical parameters in blood and also in fish tissues. Biochemical parameters such as total proteins and glucose levels, which were also investigated in the present study, are widely used as markers of water pollution (Ullah et al, 2021;Ngo et al, 2022). jms.mabjournal.com Malaysian Applied Biology…”
Section: Introductionmentioning
confidence: 95%
“…tubules in S. exigua larvae at a dosage of 44 μg/g in the first generation had lower activity than control and then increased in the second generation (Kafel et al, 2003). One of the reasons for the high activity of GST can be the high accumulation of heavy metals, such as Cd (Ngo et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the activity of GST in the midgut of fifth instar larvae and females of locusts of Aiolopus thalassinus (Orthoptera: Acrididae) collected from areas contaminated with heavy metals lead, cadmium, copper and zinc were considerably high (Abdelfattah et al, 2021), and also, GST enzyme in Malpighian tubules in S. exigua larvae at a dosage of 44 μg/g in the first generation had lower activity than control and then increased in the second generation (Kafel et al, 2003). One of the reasons for the high activity of GST can be the high accumulation of heavy metals, such as Cd (Ngo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the circulatory system and nervous tissue is also recorded in human due to chromium toxicity. Cr in the presence of other metals has been shown to increase glycogen levels in numerous organs that are stressed due to metal exposure (Ngo et al, 2022).…”
Section: Chromium (Cr)mentioning
confidence: 99%